PEMBERDAYAAN SUMBER DAYA SEKOLAH MELALUI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH - Dwi Deswary (Jurnal Manajemen Pendidikan, 2012)
In implementation MBS is needed strong leadership, that is have ability move resources to reach study target by applying â€œFour Eâ€™s of Leadershipâ€ (Energy, Energize, Edge, & Execution). Implementation MBS needs involvement of all resources that have ability empowering and willingness for used by school chronically by applying approach of quality problem solution (integrated management problem solving). Quality Improvement institute education must began with strategic activity of plan compilation that entangle all stakeholderses that exist in school or stakeholders that can used by the party of school. Strategic plan Compilation school that entangle stakeholders either through internal or external must apply risk management bases on ISO 31000 and biru ocean strategy.